Molecular docking studies of BCL- 2 with Erythroxylum monogynum Roxb. compounds for anti inflammatory studies - Kumar, C. Dhanunjaya; Begum, S. Nasireen; Rao, D. Muralidhara (International Journal of Scientific Research in Biological Sciences, 2019)
Due to the presence of large number of phyto compounds the medicinal plants shows wide spread properties for diseases which are not cured by traditional medicine. In this work bioactive compounds of Erythroxylum monogynum plant extracts were selected .By the studies of Gas chromatography and mass spectrum the compounds present in Erythroxylum monogynum ethanolic extracts were identified based on retention time ,area. The compounds which were identified are used for anti inflammatory activity by insilico method with BCL-2 which plays key role in causing of inflammation. Hence this is selected for docking studies with the different compounds of Erythroxylum monogynum .The docking results showed that among compounds of Erythroxylum monogynum compounds the Cyclo Hexane, 2-Ethoxy -1-hydroxy-4-oxo-3-phntyl-32cyclobutenyl)acetate, 1,8-bis[(benzoyl)benzoyloxy]-3, 6-dioxa -octane,N-(Tetramethylpiperidinyl) ortho-fomyl benzoate , 1,30-Triacontanediol ,5-trichloro methyl-3-[1-(cyanothio)ethyl]-4, 5-dihydroisoxazol-5-ol.